Enhancing Oncology Health Care Provider’s Sensitivity to Cultural Communication to Reduce Cancer Disparities: A Pilot Study - Quinn, Gwendolyn P. (2011)
Under the auspices of a partnership grant to reduce cancer health disparities, Moffitt Cancer Center (MCC) partnered with the Ponce School of Medicine to identify the perceived cultural communication needs of MCC healthcare providers regarding Hispanic patients with limited or no English skills. Oncologists (N=72) at MCC were surveyed to identify the specific areas of cultural communication techniques for which they desired to receive additional training. The majority of participants (66%) endorsed an interest in obtaining training to communicate difficult issues (terminal illness, controversial diagnosis) in a manner respectful to Hispanic culture. A workshop was conducted with providers (N=55) to improve cultural communication between Hispanic patients and families focusing on culture, terminal illness, and communication strategies. Findings from a pre–post test indicate an overall positive response to the workshop. Results from this study can help inform future efforts to enhance cultural competency among health providers.